598 Neutrophils propagate inflammation and fibrosis in primary sclerosing cholangitis - Abid Anwar; Sofia Jerez Ortega; Maleeha Kalaiger; Kaitlin Friesland; Jordan Young; Amaury E. Tuerlinckx; Usman Yaqoob; Robert C. Huebert; Nidhi Jalan-Sakrikar (Journal of Clinical and Translational Science)
Objectives/Goals: Primary sclerosing cholangitis (PSC) manifests with an inflammatory milieu that leads to fibrotic scarring of the liver. Human PSC liver bile ducts are enriched with neutrophils; however, their infiltration and functional role is unexplored. Our goal is to investigate the mechanism and impact of peribiliary neutrophil infiltration observed in PSC. Methods/Study Population: Primary cholangiocytes (bile duct cells) isolated from WT and mouse models of PSC (3,5-diethoxycarbonyl-1,4-dihydrocollidine (DDC)-fed mice and Mdr2-/- mice) were analyzed by RNA-sequencing. Immunofluorescence (IF) was performed on liver tissues from PSC patients and mouse models of PSC for markers of bile ducts and neutrophils (KRT19 and MPO). Intrahepatic leukocytes (IHL) isolated from mice livers were evaluated for neutrophil abundance and activation state. Anti-Ly6G antibody-mediated neutrophil depletion in Mdr2-/- mice was analyzed by IF, histology, and cytometry by time-of-flight (CyTOF). Cholangiocytes stimulated with TNFα (to induce an inflammatory phenotype) were analyzed for neutrophil chemoattractants with genetic and pharmacological interventions. Results/Anticipated Results: RNA-seq analysis of primary cholangiocytes from PSC mouse models revealed enrichment in inflammatory and neutrophil degranulation pathways. Flow cytometry and RT-PCR analysis revealed an increase in the neutrophil population in PSC mice with activated phenotype. Peripheral depletion of neutrophils in Mdr2-/- mice alleviated liver injury and inflammation, along with a reduction in peribiliary neutrophil infiltration and attenuated bridging fibrosis. CyTOF analysis showed a significant reduction in CD8+ T cells upon neutrophil depletion, implying neutrophils sustain CD8+ T cells in PSC liver. Mechanistically in cholangiocytes, TNFα mediates expression of neutrophil chemoattractants, CXCL1 and CXCL8, through the cyclic GMP-AMP synthase stimulator of interferon genes (cGAS-STING) pathway. Discussion/Significance of Impact: Our findings suggest that activation of the STING pathway in cholangiocytes in cholestatic liver disease triggers an immune response resulting in peri-portal neutrophil infiltration via CXC chemokines. The sustained presence of these activated neutrophils engages the adaptive immune system to perpetuate the inflammation and fibrosis seen in PSC.